Regulation of muscle springiness and hardness: the role of myo-inositol in enhancing fish flesh texture - Meiqi Wang; Lin Feng; Pei Wu; Yang Liu; Hongmei Ren; Xiaowan Jin; Xiaoqiu Zhou; Weidan Jiang (Food Chemistry: X, 2025)
As consumer demand for high-quality aquatic products continues to rise, enhancing the flesh texture of these products, including attributes such as hardness and springiness, has become increasingly critical. To examine the beneficial impacts of myo-inositol (MI) on the flesh quality of grass carp (Ctenopharyngodon idella), six different diets containing 35 (basal diet), 98, 195, 292, 389, and 487 mg/kg of MI were used for an 8-week period. Our results demonstrate that MI supplementation (292–389 mg/kg) enhances both the springiness and hardness of fish. The increase in springiness and hardness is likely attributable to MI's promotion of elastin and collagen synthesis while simultaneously inhibiting their degradation. Furthermore, 195–487 mg/kg MI enhances fish freshness and flavor by mitigating postmortem ATP degradation and modulating the free amino acid profile. This study establishes a foundation for investigating the contribution of MI to enhancing the flesh texture of adult grass carp.